Buildup of biobased adhesive layers by enzymatically controlled deposition on the example of casein. (December 2015) - Strube, Oliver I.; Rüdiger, Arne A.; Bremser, Wolfgang
Abstract: We present a method for the enzyme mediated buildup of protein adhesive layers. The process is based on our autodeposition-like formation of biological coatings. The presented example utilizes the enzymatic destabilization of casein micelles with the aspartic protease chymosin—the same process that is used in cheesemaking. If two adjacent support surfaces with adsorbed enzyme are immersed into a casein dispersion, protein layers will form on both surfaces and eventually form an adhesive layer between them. As a proof of concept, we show that the process works as intended, and that in fact the enzymatic process is the driving force. Several parameters are examined and the resulting layers are investigated via scanning electron microscopy.